(untitled) (Journal of actual problems of jurisprudence, 2019)
In this Article its author in a historical retrospection describes speci cs of legal regulation of those aspects which relate to the use of corporate forms for legal entities to perform economic activities under Kazakhstani legislation of the soviet time. The attention is paid to the phenomena of perception of concepts of the modern corporate law from legislation of foreign jurisdictions. Based on the analysis carried out by the author with respect to foreign and Kazakstani scienti c and legal sources the author proposes his view concerning content of such legal concepts as corporate relations and a corporation. There are main legislative acts of corporate law in Kazakhstan, as well as its most noticeable features pointed out in this Article. The authors view regarding tendencies of further development of the corporate legislation in Kazakhstan, as well as directions of its reformation (modernization) is also offered.